2012
DOI: 10.1007/s10661-012-3002-5
|View full text |Cite
|
Sign up to set email alerts
|

Saturated hydraulic conductivity of soils in the Horqin Sand Land of Inner Mongolia, northern China

Abstract: Water is a limiting factor to plant growth in Horqin Sand Land of China. Knowledge of soil saturated hydraulic conductivity (K(sat)) is of importance because K(sat) influences soil evaporation and water cycling at various scales. In order to analyze the variation of K(sat) along with sand types and soil depths, and its relationship with soil physiochemical properties, six typical lands were chosen, including mobile dune, fixed dune, pine woodland, poplar woodland, grassland, and cropland, and K(sat) was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The increase of snow in winter increases the thickness of snow, soil temperature and soil water supply in early spring, and thus affects plant growth and biomass allocation (Chen et al, 2008; Wipf, 2010). However, in the study area of Inner Mongolia, strong continuous winds blow accumulated snow rapidly, while the sandy soil also has poor water holding capacity (Yao et al, 2013). As a consequence, water produced after snowmelt may migrate to deep soil layers very quickly, where plant roots may not be able to fully access this resource.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of snow in winter increases the thickness of snow, soil temperature and soil water supply in early spring, and thus affects plant growth and biomass allocation (Chen et al, 2008; Wipf, 2010). However, in the study area of Inner Mongolia, strong continuous winds blow accumulated snow rapidly, while the sandy soil also has poor water holding capacity (Yao et al, 2013). As a consequence, water produced after snowmelt may migrate to deep soil layers very quickly, where plant roots may not be able to fully access this resource.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical distribution of Ks in the forestland was different from the other land-use types. Yao et al (2013) also found different distributons of Ks in different land types and attributed this difference to wind erosion, spatial variability of the landscape, and human disturbances. Schwen et al (2014) found that the vertical distribution of hydraulic soil parameters under farmland differed distinctly from that under forestland.…”
Section: The Vertical Distribution Of Ks and Its Effect On Hydrologicmentioning
confidence: 90%
“…As one of the most spatially variable soil characteristics (Upchurch et al, 1988), K s exhibits scale dependency (Lai & Ren, 2007;Bormann & Klaasen, 2008;Fodor et al, 2011) with regard to the volume of the measured soil. Although the small cylinder might underestimate K S in the presence of macropore, it is still a widely used technique of collecting the undisturbed soil samples, especially in the high elevation, hard to reach Qilian mountain area (Lado et al, 2004;Benjamin et al, 2008;Gwenzi et al, 2011;Yao et al, 2013;Schwen et al, 2014;Shabtai et al, 2014;Fu et al, 2015;Yang et al, 2016). Facing with the physical and resource constraints in the topographically complex mountainous area, collecting the undisturbed soil samples in different layers with the small soil cores has been widely used and is more suitable to our regional scale study in the upper stream of the Heihe river watershed.…”
Section: Field Samplingmentioning
confidence: 99%
“…Polynomial fitting of K S with depth under different land covers The polynomial fitting was used to analyze the distribution pattern of K S with depth (Ibbitt & Woods, 2004;Hwang et al, 2012;Yao et al, 2013). Simple polynomial fitting (quadratic fitting and cubic fitting) and log 10 transformed polynomial fitting (quadratic fitting and cubic fitting) were applied to all the 32 profiles, and the range of root zone was also plotted for each profile to explain the vertical variation of K S (Figure 3).…”
Section: Impact Of Land Cover On K Smentioning
confidence: 99%